2018
DOI: 10.1139/cjpp-2017-0769
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment with interleukin-1 and tumor necrosis factor-alpha antagonists improve type 2 diabetes in rats

Abstract: In the present study, combined treatment with etanercept and anakinra were tested in the streptozotocin-induced diabetic rats. Forty male Wistar albino rats were divided into 5 groups: healthy control (HC), diabetic control (DC), diabetic + anakinra (DAT), diabetic + etanercept (DET), and diabetic + etanercept + anakinra (DEAT). HC and DC groups received subcutaneous (s.c.) injection with a saline solution, while DAT and DET groups received anakinra (10 mg/kg per day, s.c.) or etanercept (10 mg/kg, twice a wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Moreover, inhibiting TNF-α in psoriasis patients with MetS decreased macrophage infiltration and pro-inflammatory cytokines levels in umbilical fat (593). Interestingly, a combined inhibition of IL-1β and TNF-α was more effective in improving IR in T2D rats (594). Similarly targeting IL-6 improved IR and normalized adipokine levels in MetS and fructose-fed rats (595,596).…”
Section: New Avenues For Adipose Tissue Immunomodulation In Metabolicmentioning
confidence: 96%
“…Moreover, inhibiting TNF-α in psoriasis patients with MetS decreased macrophage infiltration and pro-inflammatory cytokines levels in umbilical fat (593). Interestingly, a combined inhibition of IL-1β and TNF-α was more effective in improving IR in T2D rats (594). Similarly targeting IL-6 improved IR and normalized adipokine levels in MetS and fructose-fed rats (595,596).…”
Section: New Avenues For Adipose Tissue Immunomodulation In Metabolicmentioning
confidence: 96%
“…Elevated levels of TNF-α are associated with an increased risk of diabetes and insulin resistance, this can be independent of obesity (34). Additionally, in animal studies, improving insulin resistance with TNF-α antagonist therapy supports the role of TNF-α in the development of T2DM (35). Furthermore, improved glycemia and beta-cell secretory function and reduced markers of systemic inflammation with the blockade of IL-1 with the synthetic IL-1 receptor antagonist anakinra is another strong evidence of the role of pro-inflammatory cytokines in T2DM (36).…”
Section: Discussionmentioning
confidence: 89%
“…It was thought that it would be better to determine the effect of bidirectional cytokine blockade together with not only histopathological but also other metabolic and molecular markers although the co-administration of anakinra and etanercept did not make a significant difference compared to other treatment groups. Similarly, a study using etanercept and anakinra together reported that it could improve insulin and blood sugar levels in Type 2 diabetic rats and that etanercept was more effective in increasing insulin (Dik et al 2018).…”
Section: Discussionmentioning
confidence: 90%